The relationship between noise level and sleep quality in wood processing factory workers - I Gusti Agung Haryawan; Ida Ayu Astiti Suadnyana; Nilam Cahaya (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Many wood processing factories use giant machines to cut or shave wood according to the required needs. When processing wood, the condition workers experience exposure related to machine-generated noise. Exposure to noise generated from the work on average > 85 dB. Conditions of working hours are also long, up to 8 hours per day. There are several impacts caused by the presence of noise, one of which is the occurrence of sleep disturbances. This study aimed to determine the relationship between noise level and workers' sleep quality at the Rana Bhumi wood processing factory, Gianyar, Bali-Indonesia. Methods: The research design was a cross-sectional study with a population of 30 samples of wood processing factory workers at Rana Bhumi, Gianyar, Indonesia, who met the inclusion and exclusion criteria. Measure noise level using a sound level meter and measurement of sleep quality using the Pittsburgh sleeping quality index (PSQI). The data were analyzed using computer software with Spearman's rank test to determine the significant relationship between noise level and sleep quality in wood processing factory workers. Results: The results showed that 30 factory workers were obtained by analyzing the relationship between noise level and sleep quality, where p=0.000 (p<0.05). Conclusion: There was a significant relationship between noise levels and sleep quality in wood processing factory workers in Rana Bhumi, Gianyar, Bali, Indonesia.